Hollow fiber nanofiltration membrane based on interfacial polymerization regulation and preparation method thereof

By introducing a eutectic solvent (DES) into the interfacial polymerization process of hollow fiber nanofiltration membranes, the diffusion and reaction of aqueous monomers can be precisely controlled, solving the problems of uncontrollability and environmental unfriendliness of the interfacial polymerization process, and realizing the preparation of high-performance and stable nanofiltration membranes.

CN121155375APending Publication Date: 2025-12-19RES CENT FOR ECO ENVIRONMENTAL SCI THE CHINESE ACAD OF SCI
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511138653.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-14
Publication Date
2025-12-19

AI Technical Summary

Technical Problem

The interfacial polymerization process of existing hollow fiber nanofiltration membranes is highly uncontrollable, lacks precise control over the microstructure of the formed separation layer, and has poor membrane performance stability. Existing control methods such as heat treatment, pH adjustment, and physical doping have environmental and safety issues.

Method used

A eutectic solvent (DES) is introduced as an aqueous phase additive. The diffusion behavior of the aqueous phase monomer is adjusted through hydrogen bond complexation structure and high viscosity characteristics. Combined with nitrogen purging process, the interfacial polymerization reaction is precisely controlled to form a uniform polyamide selective layer.

Benefits of technology

It achieves high performance, stability, and green manufacturing of hollow fiber nanofiltration membranes, improves membrane uniformity and overall integrity, and can flexibly switch between high-flux and high-retention modes, making it suitable for different application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005548918900000191
    Figure BDA0005548918900000191
  • Figure BDA0005548918900000192
    Figure BDA0005548918900000192
  • Figure BDA0005548918900000193
    Figure BDA0005548918900000193
Patent Text Reader

Abstract

The invention discloses a hollow fiber nanofiltration membrane based on interfacial polymerization regulation and a preparation method thereof. The method comprises the following steps: preparing a water phase system and an oil phase system, and sequentially injecting the water phase system and the oil phase system into a hollow fiber ultrafiltration membrane; performing interfacial polymerization reaction on the water phase system and the oil phase system on the surface of the hollow fiber ultrafiltration membrane; and drying to obtain the hollow fiber nanofiltration membrane. By adopting the method, the interception performance and flux of the nanofiltration membrane can be effectively adjusted, and the stability and applicability of the nanofiltration membrane are improved. The nanofiltration membrane is low in water contact angle and high in oil contact angle. Particularly, the surface porosity, the effective aperture, the sodium sulfate retention rate, the sodium chloride retention rate, the flux of sodium sulfate, the flux of sodium chloride and other properties of the nanofiltration membrane can be designed and accurately controlled according to requirements, and the properties of the nanofiltration membrane can be accurately designed and customized by adopting the method disclosed by the invention; the performance of the green and natural modified hollow fiber ultrafiltration membrane is realized, and an innovative solution is provided for high-salt resource recovery.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to a membrane separation technology, in particular to a hollow fiber nanofiltration membrane intervened by interfacial polymerization regulation of a eutectic solvent and a preparation method. BACKGROUND

[0002] As a new membrane separation technology between ultrafiltration and reverse osmosis, nanofiltration (NF) is gradually replacing traditional high-pollution separation processes with the advantages of high selective separation, low energy consumption and environmental friendliness, and is applied to drinking water purification (removal of hardness / organic matter), food and medicine (juice concentration, drug purification) and resource recovery (heavy metal removal). Its core features are: the membrane pore size is about 1-2 nm, the molecular cut-off is 200-1000 Da, and it can efficiently remove divalent and high valence ions and organic matter with a molecular weight of more than 200 through the Donnan effect and steric effect mechanisms, while allowing part of the monovalent ions to pass through. Nanofiltration technology operates at room temperature, without phase change and chemical reaction, can maintain the activity of substances, and the operating pressure is only 50-70% of that of reverse osmosis, combining the advantages of separation efficiency and economy.

[0003] Most of the nanofiltration membranes on the market are flat or spiral-wound, while hollow fiber nanofiltration membranes have the characteristics of strong resistance to pollution, high mechanical strength, and large specific surface area due to their self-supporting structure, which can provide higher water production efficiency. The characteristics of no supporting device occupying internal space, fine fibers and high packing density of hollow fiber nanofiltration membranes give them better pressure resistance and anti-pollution ability than spiral-wound membranes, especially suitable for strong water flushing scenes, and have become a hot research direction.

[0004] The interfacial polymerization method has become the mainstream process for preparing hollow fiber nanofiltration membranes due to its high structural designability, good base film adaptability and fast membrane formation. However, in the hollow fiber structure, the performance improvement still faces significant challenges. The curved surface characteristics of the hollow fiber membrane cause a gradient difference in the radial distribution of the water phase monomer, which exacerbates the complex coupling between the monomer concentration ratio, diffusion kinetics and additive synergistic effect in the reaction process, becoming the core bottleneck restricting the preparation of high-performance hollow fiber nanofiltration membranes by interfacial polymerization, and limiting its further industrial application.

[0005] To mitigate the problems of runaway reactions and structural defects during interfacial polymerization, existing research has attempted to optimize the interfacial polymerization process of hollow fiber nanofiltration membranes from multiple directions. One approach involves controlling the environmental conditions of the interfacial polymerization reaction, such as promoting the polymerization reaction through heat treatment or improving monomer dissociation and interfacial reactivity by adjusting the pH of the aqueous phase (e.g., patent CN116850793A). While these methods have improved membrane performance to some extent, they also have significant limitations. For example, heat treatment consumes a lot of energy and is prone to inducing side reactions, while pH control under strong acid / base conditions can lead to equipment corrosion and wastewater treatment problems, limiting their process stability and industrial applicability. Another common strategy is the introduction of synergistic materials through physical doping, including nanoparticles (such as Ag, TiO2, SiO2, etc.) (e.g., patent CN115090130B) and porous organic polymer particles (such as COF, MOF, etc.) (e.g., patent CN114471200A), in order to enhance the functionality and stability of the selective layer during the interfacial reaction. However, these materials often face problems such as agglomeration, uneven dispersion, and poor compatibility with polyamide layers. Some inorganic particles (such as Ag) also pose risks of oxidative deactivation and potential toxicity, affecting the long-term operational stability and safety of the membrane. In recent years, solvent-based regulation strategies have become mainstream, such as introducing ionic liquids and co-solvents (such as ethanol, DMF, DMSO) (e.g., patent CN118718762A) to adjust monomer diffusion rates and interfacial reaction behavior, thereby improving membrane structure and performance. Although these methods have a certain degree of adjustability and process versatility, they still have potential risks such as difficulty in residue treatment and environmental toxicity, or high costs, making it difficult to achieve green, efficient, and sustainable control of the interfacial polymerization process.

[0006] Based on this, this invention innovatively proposes to introduce a "deep eutectic solvent" (DES) as an interfacial reaction regulating medium in the interfacial polymerization process for preparing hollow fiber nanofiltration membranes. This overcomes the shortcomings of existing technologies in terms of safety, environmental friendliness, and controllability of interfacial reactions, thereby improving the consistency of membrane performance and the industrial adaptability of the preparation process. The DES consists of hydrogen bond acceptors (such as choline chloride, tetramethylammonium chloride, etc.) and hydrogen bond donors (such as glycerol, urea, lactic acid, etc.) in a specific molar ratio, forming a stable liquid phase system through interactions such as hydrogen bonds and van der Waals forces. Its strong hydrogen bond network can regulate the diffusion behavior of aqueous monomers in the interfacial polymerization reaction, while its high viscosity can slow down the reaction rate and reduce the risk of forming membrane pore defects, thereby achieving precise control over the polyamide layer structure.

[0007] Furthermore, DES possesses comprehensive advantages such as simple preparation (no additional chemical reaction steps required), low cost, good water solubility, and biodegradability, aligning with the development direction of green membrane materials. Although existing studies have used DES for reverse osmosis membrane surface modification and flat-sheet nanofiltration membrane preparation, this invention introduces it into the interfacial polymerization process to prepare hollow fiber nanofiltration membranes. The aim is to guide the orderly distribution and interfacial reaction of aqueous monomers on the hollow fiber membrane surface through the physicochemical properties of DES, achieving synergistic optimization of polyamide selective layer thickness, pore structure, and compactness across multiple dimensions. This provides a new green pathway for the controllable construction of high-performance hollow fiber nanofiltration membranes. [Summary of the Invention]

[0008] The purpose of this invention is to overcome the problems of high uncontrollability, lack of precise control over the microstructure of the formed separation layer (polyamide layer), and poor membrane performance stability in the existing interfacial polymerization process for preparing hollow fiber nanofiltration membranes. Addressing the limitations of existing interfacial polymerization control methods (such as heat treatment, pH adjustment, physical doping, and traditional solvent intervention) in terms of reaction precision, material compatibility, and environmental friendliness, this invention proposes a novel control approach: introducing a eutectic solvent (DES) as an aqueous phase additive. Its hydrogen-bonded complex structure and high viscosity can effectively regulate the diffusion behavior of aqueous monomers at the interface, delaying the interfacial polymerization rate and thus improving membrane uniformity and overall integrity. By combining DES with aqueous-oil phase injection time control and nitrogen purging, the retention performance of the separation layer membrane formed by the interfacial polymerization reaction can be flexibly switched to meet different application switching needs, such as high-flux and high-retention modes.

[0009] To achieve the objectives of this invention, one aspect of this invention provides a method for preparing a hollow fiber nanofiltration membrane based on interfacial polymerization regulation, comprising:

[0010] First, prepare an aqueous system by mixing an aqueous amine solution with a eutectic solvent.

[0011] Next: the acyl halide compound is mixed with an organic solvent, dissolved, and prepared into an oil phase system;

[0012] Then, the aqueous phase system and the oil phase system are injected into the hollow fiber ultrafiltration membrane in sequence. The acyl halide compounds in the oil phase system and the amine compounds in the aqueous phase system undergo interfacial polymerization on the surface of the hollow fiber ultrafiltration membrane to form a polyamide selective film, thus obtaining a hollow fiber nanofiltration membrane based on interfacial polymerization control.

[0013] The amine aqueous solution is prepared by mixing a polyamine compound with deionized water, wherein the mass percentage concentration of the polyamine compound in the amine aqueous solution is (0.45-1.5) wt%, preferably 0.45-0.6 wt%, and more preferably 0.6 wt%.

[0014] In particular, the acyl halide compound is one or more of the following: trimesoyl chloride (TMC), isophthaloyl chloride, terephthaloyl chloride, 1,3,5-cyclohexanetricarboxyl chloride, or 1,2,3,4-cyclohexanetetracarboxyl chloride, preferably trimesoyl chloride; the organic solvent is one or more of the following nonpolar solvents: n-hexane, isooctane, cyclohexane, n-octane, or n-nonane, preferably n-hexane.

[0015] Another aspect of the present invention provides a method for preparing a hollow fiber nanofiltration membrane based on interfacial polymerization regulation, comprising the following steps:

[0016] 1) Preparation of eutectic solvent

[0017] The hydrogen bond donor and the hydrogen bond acceptor are mixed evenly to prepare a eutectic solvent.

[0018] 2) Preparation of aqueous system

[0019] A eutectic solvent is added to an aqueous amine solution and mixed thoroughly to prepare an aqueous system.

[0020] 3) Preparation of oil phase system

[0021] The acyl halide compound is dissolved in an organic solvent, mixed thoroughly, and prepared into an oil phase system;

[0022] 4) Interfacial polymerization reaction

[0023] 4-1) Inject the aqueous phase system into the inner cavity of the hollow fiber ultrafiltration membrane from one end, that is, inject the aqueous phase system into the inner cavity of the ultrafiltration membrane from the injection end of the base membrane. At the same time, observe the outflow of the aqueous phase system from the other end of the base membrane, that is, the outflow end of the base membrane. Start timing when the aqueous phase system flows out from the outflow end of the base membrane at a stable flow rate. This is recorded as the time for the aqueous phase to drop steadily.

[0024] 4-2): After the aqueous phase is stabilized and dripped for 2-7 minutes, the aqueous phase system is injected into the base membrane cavity for 2-7 minutes. After the aqueous phase fills and wets the base membrane cavity, the injection of the aqueous phase system into the base membrane cavity is stopped, and nitrogen gas is introduced into the base membrane cavity from the base membrane injection end to perform nitrogen purging treatment after aqueous phase injection.

[0025] 4-3) After nitrogen purging, the oil phase system is injected into the inner cavity of the hollow fiber ultrafiltration membrane from the injection end, that is, the oil phase system is injected into the inner cavity of the ultrafiltration membrane from the injection end of the base membrane. At the same time, the outflow of the oil phase system at the other end of the base membrane, that is, the outflow end of the base membrane, is observed. The timer starts when the oil phase system flows out from the outflow end of the base membrane at a stable flow rate, and is recorded as the oil phase stable droplet time.

[0026] 4-4) The oil phase is stabilized and dripped for 2-7 minutes. That is, the oil phase system is injected into the inner cavity of the base membrane for 2-7 minutes. The oil phase fills and wets the inner cavity of the base membrane. The acyl halide compounds in the oil phase system and the polyamine compounds in the aqueous phase system in the hollow fiber ultrafiltration membrane undergo interfacial polymerization reaction on the surface of the hollow fiber ultrafiltration membrane to form a polyamide selective film.

[0027] 4-5) After the interfacial polymerization reaction for 2-7 minutes, stop injecting the oil phase system into the inner cavity of the base membrane, and introduce nitrogen gas into the inner cavity of the base membrane from the injection end of the base membrane to perform nitrogen purging treatment after oil phase injection.

[0028] In step 1), the hydrogen bond donor is an organic small molecule compound having hydroxyl, carboxyl, amino, or amide groups; and the hydrogen bond acceptor is a quaternary ammonium salt compound.

[0029] In particular, the hydrogen bond donor is preferably one or more of urea, glycerol, polyethylene glycol, and citric acid.

[0030] In particular, the quaternary ammonium salt compound is one or more of choline chloride, tetramethylammonium chloride, ethyltrimethylammonium chloride, tetrabutylammonium bromide, and betaine.

[0031] In particular, the eutectic solvent system is preferably a choline chloride / urea system, a betaine / glycerol system, or a tetrabutylammonium bromide / polyethylene glycol system.

[0032] Specifically, in the choline chloride / urea system, the molar ratio of choline chloride to urea is 1:(1.5-2.5), preferably 1:2; in the betaine / glycerol system, the molar ratio of betaine to glycerol is 1:(2-3), preferably 1:2.5; and in the tetrabutylammonium bromide / polyethylene glycol system, the molar ratio of tetrabutylammonium bromide to polyethylene glycol is 1:(3-4), preferably 1:3.5. The optimal molar ratios for the above-mentioned optimal eutectic solvent systems were determined by differential scanning calorimetry (DSC) and melting point method to determine the eutectic point of the system. The optimal molar ratios result in the lowest melting point and maintain a stable hydrogen bond network.

[0033] In particular, the number average molecular weight of the polyethylene glycol is 200-600, preferably 400.

[0034] In particular, the hydrogen bond donor and the hydrogen bond acceptor are mixed uniformly under stirring, wherein the mixing temperature is 40-60℃, preferably 50±2℃; the stirring rate is 250-370rpm, preferably 300±50rpm; and the stirring time is 0.75-2h, preferably 1-1.5h.

[0035] In step 1), the hydrogen bond donor and hydrogen bond acceptor are mixed in a molar ratio. This molar ratio is determined based on the hydrogen bond network equilibrium required for the formation of a stable, transparent liquid from the eutectic solvent. The hydrogen bond donor (e.g., urea) provides a large number of -NH and C=O sites, while the hydrogen bond acceptor provides positively charged quaternary ammonium cations and Cl-. - Anions act as hydrogen bond anchors. When the molar ratio is close to 1:2, the system has moderate viscosity and good flowability, and can form a stable, uniform, transparent eutectic phase at room temperature, which is beneficial for controlling monomer diffusion and polyamide structure during subsequent interfacial polymerization. If the molar ratio is too low, the hydrogen bond network is insufficient, leading to phase separation. If the molar ratio is too high, the system viscosity is too high, which is not conducive to film formation.

[0036] Different molar ratios of hydrogen bond acceptors and donors in eutectic solvents affect the viscosity, polarity, and hydrogen bond complexation ability of DES, thereby regulating the diffusion behavior of DES in the aqueous phase and the film formation rate and compactness at the monomer reaction interface in the oil phase. Magnetic stirring was performed at specific temperature conditions (40-60℃) and stirring speed (200-500 rpm) for a certain time (0.75-2 hours) until a transparent and homogeneous liquid was formed, yielding DES. Subsequently, vacuum drying was carried out at -0.08 MPa and 40℃ for 24 hours to remove residual trace amounts of moisture. The DES was then obtained. Stirring temperature, time, and rate are important process parameters for DES preparation. If the stirring temperature is too low (<40℃), the hydrogen bond acceptors and donors may not dissolve sufficiently or hydrogen bond complexation may be insufficient; if the temperature is too high (>60℃), some components may undergo thermal decomposition or water loss, thereby compromising the stability of the DES system. Insufficient stirring time or too low a speed may lead to uneven mixing, local phase separation, and the formation of microemulsions; excessive stirring may result in excessive dissolved oxygen or local crystallization. Therefore, precise control of stirring temperature, time, and speed is a crucial prerequisite for ensuring the uniformity of DES and the controllability of the subsequent interfacial polymerization process of the stabilizer. Improper control of these parameters will directly affect the structural integrity of the hollow fiber nanofiltration membrane and the repeatability and stability of membrane separation performance.

[0037] In particular, it also includes step 1A), pretreatment of the hollow fiber ultrafiltration membrane by placing the hollow fiber ultrafiltration membrane in ultrapure water and ultrasonically cleaning it; then using nitrogen to dry the moisture in the inner cavity of the hollow fiber ultrafiltration membrane.

[0038] In particular, the ultrasonic cleaning time is 20-40 minutes, preferably 30 minutes.

[0039] In particular, the relative pressure of nitrogen during the nitrogen purging process is 0.08-0.1 MPa; the purging time is 3-5 min.

[0040] The standard for nitrogen drying is that if no water droplets or mist appear within 30 seconds after blowing nitrogen to the membrane outlet, it is considered dry.

[0041] In particular, in step 2), the mass ratio of the eutectic solvent to the amine aqueous solution in the aqueous phase system is (0.2-2.0):100, preferably (0.2-1.0):100, and more preferably 0.5:100.

[0042] In particular, the amine aqueous solution described in step 2) is prepared by mixing a polyamine compound with deionized water, wherein the mass percentage concentration of the polyamine compound in the amine aqueous solution is (0.45-1.5) wt%.

[0043] In particular, the polyamine compound is one or more of piperazine (PIP), p-phenylenediamine, p-xylenediamine, cyclohexanediamine, branched or dendritic polyethyleneimine, preferably piperazine.

[0044] In particular, the mass fraction of the polyamine compound is preferably 0.45-0.6 wt%, more preferably 0.6 wt%.

[0045] In particular, the acyl halide compound mentioned in step 3) is one or more of the following: trimesoyl chloride (TMC), isophthaloyl chloride, terephthaloyl chloride, 1,3,5-cyclohexanetricarboxyl chloride or 1,2,3,4-cyclohexanetetracarboxyl chloride, preferably trimesoyl chloride; the organic solvent is one or more of the following nonpolar solvents: n-hexane, isooctane, cyclohexane, n-octane or n-nonane, preferably n-hexane.

[0046] In particular, the mass percentage concentration of the acyl halide compound in the oil phase system is (0.1-1) wt%, preferably 0.15 wt%.

[0047] In particular, the injection rate of the aqueous phase system in step 4-1) is 0.5-2 mL / min, preferably 1-2 mL / min, and more preferably 1.5 mL / min.

[0048] The hollow fiber ultrafiltration membrane (i.e., the base membrane) is one or more of polyethersulfone (PES), polysulfone (PSF), polyacrylonitrile (PAN), polypropylene (PP), polyethylene (PE), polystyrene (PS), polycarbonate (PC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE) or polyamide imide (PAI) hollow fiber filter membranes, preferably a membrane layer formed of PES, PSF or their copolymers.

[0049] In particular, the hollow fiber ultrafiltration membrane described in step 4-1) has a molecular weight cutoff of 5-20 kDa, an inner diameter of 0.8-1.2 mm, and a wall thickness of 200-300 μm.

[0050] In particular, the timing of the stable droplet formation in step 4-1) is as follows: timing begins when the aqueous system flows out of the ultrafiltration membrane at a flow rate of 1-3 drops / second, i.e., when a stable droplet is formed. In other words, timing begins when the flow rate of the aqueous system flowing out of the ultrafiltration membrane reaches 1-3 drops / second.

[0051] In particular, when the aqueous phase system flows out from the other end of the ultrafiltration membrane (i.e., the outflow end), and the flow rate of the aqueous phase system droplets is 1-3 drops / second, and regular droplets are formed within 10-15 seconds (with the interval between consecutive droplets fluctuating ≤±20%), this is recorded as the starting point for the stable droplet timing of the aqueous phase.

[0052] In particular, the time for the aqueous phase to stabilize the dripping time is the time it takes for the aqueous phase system to fill the inner cavity of the hollow fiber ultrafiltration membrane, which is the time it takes for the aqueous phase system to wet the inner cavity of the ultrafiltration membrane, and the time from when the aqueous phase system fills the inner cavity of the ultrafiltration membrane to when the vertical system discharges from the inner cavity of the ultrafiltration membrane.

[0053] An aqueous phase is introduced into the injection end of the base membrane, and the aqueous phase flows out from the outflow end of the base membrane. Timing begins when the outflow rate of the aqueous phase droplets from the outflow end of the base membrane stabilizes at 1-3 drops / second, that is, when a stable droplet is formed at the other end of the base membrane. This is also known as the aqueous phase stable droplet timing. The aqueous phase system fills the inner cavity of the base membrane when a stable droplet is formed at the other end of the base membrane.

[0054] In particular, in step 4-2), the timing of the aqueous phase stable droplet is 2-7 minutes, which means that the aqueous phase system is kept full in the inner cavity of the base membrane for 2-7 minutes. That is, the timing starts when the aqueous phase system flows out of the other end of the base membrane at a flow rate of 1-3 drops / second, and the flow rate is kept at 1-3 drops / second for 2-7 minutes.

[0055] In particular, the time for the aqueous phase to stabilize during the dripping in step 4-2) is 2-7 minutes, which is the time for the aqueous phase system to fill and enter the inner cavity of the base membrane.

[0056] Starting from the beginning of the aqueous phase steady-state dripping timer, continue to maintain the aqueous phase system in the hollow fiber ultrafiltration membrane (also known as the base membrane) for 2-7 minutes until the aqueous phase fills and wets the base membrane cavity. After the set time is reached, immediately stop the aqueous phase injection and purge the residual aqueous phase system in the membrane cavity by introducing nitrogen gas.

[0057] In particular, for the preparation of high-retention-capacity nanofiltration membranes, the timing time for stable dripping in the aqueous phase is 4-7 min, preferably 5 min; the timing time for stable dripping in the oil phase is 4-7 min, preferably 5 min.

[0058] In particular, for the preparation of high-flux nanofiltration membranes, the timing time for stable dripping in the aqueous phase is 2-4 min, preferably 3 min; the timing time for stable dripping in the oil phase is 2-4 min, preferably 3 min.

[0059] In particular, during the nitrogen purging process after aqueous phase injection, the relative pressure of nitrogen is 0.06-0.1 MPa; the purging time is 2-6 min, preferably 3 min.

[0060] Specifically, in step 4-2), the relative pressure of nitrogen during the nitrogen purging process is 0.08±0.02MPa; the nitrogen purging time is 2-6 min. In step 4-3), the oil phase system injection rate is 0.5-2 mL / min; in step 4-4), the interfacial polymerization reaction time is 2-7 min.

[0061] In particular, the injection rate of the oil phase system in step 4-3) is preferably 1-2 mL / min, and more preferably 1.5 mL / min.

[0062] In particular, the ratio of nitrogen purging time to oil phase injection time in step 4-3) is 1:(0.5-1).

[0063] The oil phase stable drop time is 2-7 minutes, which means the oil phase system fills and enters the inner cavity of the base film in 2-7 minutes. This means that the interfacial polymerization reaction occurs during the process of the oil phase filling and wetting the inner cavity of the base film, which is the interfacial polymerization reaction time of 2-7 minutes.

[0064] The advantage of this invention over existing interfacial polymerization reactions is that it does not require control of the interfacial polymerization reaction environment (heat treatment, pH), and can be carried out at room temperature.

[0065] Timing begins when the droplet flow rate stabilizes, and is determined from the starting point of the timing process. The time it takes for the oil phase to be introduced is the interfacial polymerization reaction time.

[0066] In particular, the timing of the stable droplet formation of the oil phase in step 4-3) is as follows: timing begins when the oil phase system flows out from the outlet of the ultrafiltration membrane and the flow rate of the oil phase system is 1-3 drops / second, that is, when a stable droplet is formed. In other words, timing begins when the flow rate of the oil phase system flowing out from the outlet of the ultrafiltration membrane reaches 1-3 drops / second.

[0067] In particular, when the oil phase system flows out from the other end of the ultrafiltration membrane (i.e., the outflow end), and the flow rate of the oil phase system droplets is 1-3 drops / second, and regular droplets are formed within 10-15s (with the interval between consecutive droplets fluctuating ≤±20%), this is recorded as the starting point for the stable droplet timing of the oil phase.

[0068] In particular, the time for the oil phase to stabilize during dripping is the time it takes for the oil phase system to fill the inner cavity of the hollow fiber ultrafiltration membrane, which is the time it takes for the oil phase system to wet the inner cavity of the ultrafiltration membrane, and the time from when the oil phase system fills the inner cavity of the ultrafiltration membrane to when the vertical system discharges from the inner cavity of the ultrafiltration membrane.

[0069] After the aqueous phase is injected, nitrogen is purged until the aqueous phase is basically emptied (no more droplets flow continuously from the outlet, and the droplet flow frequency is less than 1 drop / 5s within 10s, with only intermittent micro-mist airflow carrying it out) to ensure that the surface of the membrane cavity is uniformly moistened but without free liquid retention.

[0070] In step 4-4), the timing of the stable dripping of the oil phase system is the same as that of the stable dripping of the water body. The time for the oil phase to enter the inner cavity of the ultrafiltration support membrane is the interfacial polymerization reaction time.

[0071] The so-called "stable droplet" refers to an aqueous or oil phase system flowing out from the other end of the base film at a constant flow rate of 1-3 drops / second.

[0072] The timing of a stable droplet in an aqueous phase is started from the moment a stable droplet forms in the aqueous phase system.

[0073] Start timing after the liquid has stabilized and stop introducing the aqueous or oil phase after 2-7 minutes.

[0074] In particular, the timing of the oil phase stabilization drop in step 4-4) is the interfacial polymerization reaction time, which is 2-7 min.

[0075] In particular, for the preparation of high-retention-capacity nanofiltration membranes, the interfacial polymerization reaction time is 4-7 min, preferably 5 min; for the preparation of high-flux nanofiltration membranes, the interfacial polymerization reaction time is 2-4 min, preferably 3 min.

[0076] In particular, in steps 4-5), nitrogen gas is introduced into the inner cavity of the hollow fiber ultrafiltration membrane for nitrogen purging treatment, which terminates the interfacial polymerization reaction.

[0077] In particular, during the nitrogen purging process after oil phase injection in steps 4-5), the relative pressure of nitrogen is 0.06-0.1 MPa; the purging time is 1-4 min.

[0078] In particular, for the preparation of high rejection nanofiltration membranes, the nitrogen purging time after oil phase injection is 2-4 min, preferably 3 min; for the preparation of high flux nanofiltration membranes, the nitrogen purging time after oil phase injection is 1-2 min, preferably 1 min.

[0079] After the oil phase is injected, the nitrogen purging process is carried out until the water-oil phase is basically emptied (the droplets no longer flow continuously from the outlet end, and the droplet flow frequency is less than 1 drop / 5s within 10s, with only intermittent micro-mist airflow carrying out the droplets). After that, the membrane is placed at room temperature to dry for a certain period of time to obtain the hollow fiber nanofiltration membrane based on interfacial polymerization control.

[0080] In particular, the ratio of nitrogen purging time in step 4-5) to nitrogen purging time in step 4-2) is 1:(1-3), preferably 1:3.

[0081] In particular, it also includes steps 4-6) drying treatment, in which the hollow fiber ultrafiltration membrane after the termination of the interfacial polymerization reaction is allowed to stand at room temperature for at least 4 hours.

[0082] In another aspect, the present invention provides a hollow fiber nanofiltration membrane based on interfacial polymerization control prepared according to the above method.

[0083] In particular, the functional layer of the hollow fiber nanofiltration membrane is composed of cross-linked polyamide formed by interfacial polymerization of polyamine compounds and acyl halide compounds, with a thickness of 80-180 nm; surface porosity of 30-50%; effective pore size of 0.6-2.2 nm; water contact angle of the nanofiltration membrane of 30-55°; underwater oil contact angle ≥150°; surface zeta potential of -15 to -45 mV; Na2SO4 rejection rate adjustable range of 45-98%, flux adjustable range of 20-60 L / (m2·h); NaCl rejection rate adjustable range of 10-50%, flux adjustable range of 20-60 L / (m2·h). 2 ·h).

[0084] In the interfacial polymerization process of this invention, an excess of amine is required to ensure complete reaction of the acyl halide. During interfacial polymerization, the diffusion of amine into the organic phase is the rate-controlling step. In the crosslinked polyamide functional layer, the mass ratio of polyamine compound to acyl halide compound is (5–20):1, preferably (8–12):1. If the amine / acyl halide mass ratio is <5:1 (insufficient molar equivalent of amine groups), acyl halide residue occurs, resulting in "end" defects in the crosslinked network, a loose skin layer, and a decreased retention rate. An upper limit of 20:1 prevents excessive crosslinking and pore blockage. When the amine / acyl halide ratio is >20:1, the amine concentration on the membrane surface is extremely high, generating an excessively thick and dense crosslinked layer. Simultaneously, unreacted amine undergoes secondary polymerization within the pores, leading to excessively low pure water flux. A preferred ratio of 8–12:1 balances flux and retention within this range, with an amine to acyl halide molar ratio of approximately 2–3:1. This ensures complete consumption of the acyl halide while controlling the crosslinked layer thickness to 100–200 nm, forming a dense, defect-free skin layer.

[0085] The hollow fiber nanofiltration membrane of the present invention is composed of a cross-linked polyamide functional layer formed on the surface of a polyether sulfone (PES) ultrafiltration base membrane. The thickness of the functional layer is 80-180 nm, the surface porosity is 30-50%, and the effective pore size adjustment range is 0.6-2.2 nm (corresponding to a molecular weight cutoff threshold MWCO 200-1000 Da).

[0086] In the preparation process of the hollow fiber nanofiltration membrane of the present invention, the membrane formation process is precisely adjusted by controlling the water phase / oil phase injection time ratio and the low co-soluble solvent concentration, thereby achieving effective control of membrane structure and separation performance to adapt to different working conditions.

[0087] The nanofiltration membrane of this invention possesses superhydrophilic-superoleophobic properties, with a water contact angle of 30-55°; an underwater oil contact angle ≥115°; a surface zeta potential of -15 to -45 mV; and a charge density of (1.0-2.5) × 10⁻³ C / m³. 2 The membrane exhibits adjustable rejection rates for sodium sulfate (45-98%) and flux (20-60 L / (m²·h)); and adjustable rejection rates for sodium chloride (10-50%) and flux (25-60 L / (m²·h)). Its structure comprises a highly cross-linked dense layer and a porous ultrafiltration support layer. Through kinetic control during interfacial polymerization, the pore size and surface charge distribution of the membrane can be adjusted within a certain range. While maintaining a roughly constant rejection rate for divalent anions, the membrane's permeability is significantly improved, thus alleviating to some extent the trade-off between rejection rate and flux in traditional membranes. It possesses the potential for application in high-salinity wastewater treatment and ion-selective separation.

[0088] Compared with the prior art, the present invention has the following beneficial effects:

[0089] This invention overcomes the traditional path of interfacial polymerization processes that relies on interfacial polymerization environment modification (pH, heat treatment), physical doping, and ordinary solvent modification by synergistically optimizing the hydrogen bonding regulation characteristics of eutectic solvent (DES) and aqueous / oil phase injection time. It directly constructs a nanofiltration functional layer with designable performance on commercial ultrafiltration membranes. DES, as an aqueous phase additive, combined with injection time adjustment, precisely regulates monomer diffusion-crosslinking kinetics, endowing the PA layer (ultrathin polyamide selective layer) with a dynamically tunable pore size gradient (0.6-1.8 nm) and charge density (-15 to -45 mV).

[0090] This invention utilizes a mechanism of synergistic regulation of eutectic solvent intervention and injection time parameters (not a single chemical modification) to achieve adjustable control of membrane structure and separation performance without changing the base membrane material. This allows the same base membrane to be used to derive functional membrane layers suitable for different separation scales (sodium sulfate rejection rate difference >40%, flux increase 50-120%). Furthermore, through the biodegradability of DES and zero wastewater discharge, it also possesses the advantages of green manufacturing, significantly improving industrial adaptability and operational stability, and providing efficient and flexible solutions for complex scenarios such as high-salinity wastewater treatment and drug molecular sieving. [Attached Image Description]

[0091] Figure 1The figure shows the experimental results of the rejection rate of sodium sulfate and sodium chloride by the hollow fiber nanofiltration membrane based on interface polymerization regulation of the present invention.

[0092] Figure 2 The figure shows the experimental results of the permeation flux test of sodium sulfate and sodium chloride by the hollow fiber nanofiltration membrane based on interface polymerization regulation according to the present invention.

Detailed Implementation Methods

[0093] The principles and features of the present invention are described in conjunction with the following embodiments. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention.

[0094] Example 1: Preparation of high-capacity hollow fiber nanofiltration membrane

[0095] In the process of preparing hollow fiber nanofiltration membranes by interfacial polymerization, the aqueous phase injection time (stable dripping time of aqueous phase), the oil phase injection time (stable dripping time of oil phase), and the nitrogen purging time have a significant impact on the membrane structure and separation performance.

[0096] High-retention membranes (such as those in Example 1) typically employ longer aqueous phase contact times (preferably 5 min, applicable range 4–7 min), longer oil phase contact times (preferably 5 min, applicable range 4–7 min), and longer third nitrogen purging times (preferably 3 min, applicable range 2–4 min) to promote the full enrichment and deep diffusion of hydrophilic monomers on the membrane surface, thereby forming a thicker polyamide selective layer with a higher degree of crosslinking and achieving a higher solute retention rate.

[0097] High-flux membranes (such as those in Example 1A) employ shorter aqueous phase contact times (preferably 3 min, applicable range 2–4 min), shorter oil phase contact times (preferably 3 min, applicable range 2–4 min), and shorter third nitrogen purging times (preferably 1 min, applicable range 1–2 min) to control the accumulation and crosslinking degree of monomers at the interface, forming a relatively loose and thin selective layer, thereby increasing water flux.

[0098] 1. Pretreatment of the base film

[0099] A commercially available polyethersulfone (PES) hollow fiber ultrafiltration membrane (referred to as the base membrane, MWCO 10kDa, inner diameter 1.2mm, outer diameter 1.8mm, wall thickness 300μm) is ultrasonically cleaned with ultrapure water at room temperature (usually 25±5℃) for 30 min (usually 20-40 min). Subsequently, the hollow fiber ultrafiltration base membrane is dried by blowing nitrogen gas at a relative pressure of (0.08±0.02)MPa, which is the first nitrogen purging treatment. The first nitrogen purging treatment time is 3 min (usually ≥3 min, preferably 3-5 min) until the inner surface of the membrane cavity is dry and no water droplets are dripping from the outlet end of the base membrane. The pretreated hollow fiber ultrafiltration base membrane (i.e., the pretreated base membrane, hollow fiber ultrafiltration support membrane) is prepared for use.

[0100] The first purging treatment involves using nitrogen gas at a relative pressure of 0.08 MPa ± 0.02 MPa for ≥3 minutes (preferably 3-5 minutes) until no visible droplets are visible at the outflow end within 30 seconds, thus completely removing moisture from the membrane. Ultrasonic cleaning of the base membrane is mainly to remove dust, residual solvents, and impurities from the surface and pores, ensuring a clean base membrane surface and unobstructed pores, thereby providing conditions for uniform monomer penetration. Subsequent nitrogen purging effectively removes excess liquid from the pores, preventing residual cleaning solution from affecting the solution wetting and diffusion process, and reducing the reintroduction of impurities or moisture during operation, keeping the base membrane in a stable initial state.

[0101] In the specific embodiments of this invention, the hollow fiber ultrafiltration base membrane (support layer) is illustrated using a polyethersulfone hollow fiber filter membrane as an example. Other hollow fiber filter membranes are also applicable to this invention, such as polysulfone (PSF), polyacrylonitrile (PAN), polypropylene (PP), polyethylene (PE), polystyrene (PS), polycarbonate (PC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), or polyamide imide (PAI), etc.

[0102] The PES hollow fiber ultrafiltration membrane selected in this embodiment has a molecular weight cutoff (MWCO) of 10 kDa, an inner diameter of 1.2 mm, an outer diameter of 1.8 mm, and other inner diameters of 0.8-1.2 mm; a wall thickness of 200-300 μm; hollow fiber ultrafiltration membranes with a molecular weight cutoff of 5-20 kDa are also suitable for this invention.

[0103] 2. Preparation of eutectic solvent (DES)

[0104] Accurately weigh 6.981 g of choline chloride and 6.006 g of urea (molar ratio 1:2), mix them, and stir continuously for 1.5 hours in a constant temperature magnetic stirrer (IKA RCT basic, speed 350±20 rpm) at 50±2℃ until a homogeneous, transparent, viscous liquid is formed, thus obtaining the urea-choline chloride eutectic solvent (DES).

[0105] In this embodiment, choline chloride is used as the acceptor and urea as the hydrogen bond donor. DES prepared with a molar ratio of choline chloride to urea of ​​1:(1.5-2.5) is applicable to this invention.

[0106] Different molar ratios of hydrogen bond donors and acceptors in DES will affect the viscosity, polarity, and hydrogen bond complexation ability of DES, thereby regulating the diffusion behavior of DES in the aqueous phase and the film formation rate and compactness at the monomer reaction interface in the oil phase.

[0107] In the preparation of DES, stirring temperature, time, and rate are crucial process control parameters. If the stirring temperature is too low (<40℃), hydrogen bond acceptors and donors may not dissolve sufficiently, or hydrogen bond complexation may be inadequate. If the temperature is too high (>60℃), some components may undergo thermal decomposition or water loss, thus compromising the stability of the DES system. Insufficient stirring time (less than 1 hour) or too low a speed (below 330 rpm) may lead to uneven mixing, localized phase separation, and the formation of a microemulsion instead of a liquid. Excessive stirring time (more than 2 hours) or over-stirring (stirring rate above 370 rpm) can result in excessive dissolved oxygen in the DES solvent or localized crystallization. (Dissolved oxygen will undergo a slow oxidation reaction with amine monomers (such as piperazine) during subsequent interfacial polymerization, causing a decrease in monomer activity; the precipitated crystals will block the pores of the base film or deposit on the base film surface, forming physical barriers and resulting in uneven interfacial polymerization layer thickness and localized film failure.) Therefore, precise control of stirring temperature, time, and rate is a crucial prerequisite for ensuring the uniformity and stability of DES and the controllability of subsequent interfacial polymerization processes. If the above parameters (stirring temperature, time, rate, and the molar ratio of hydrogen bond donors to hydrogen bond acceptors) are not properly controlled, the structural integrity of the hollow fiber nanofiltration membrane and the repeatability and stability of the membrane separation performance will be directly affected.

[0108] The DES system of this invention is illustrated using choline chloride / urea (molar ratio 1:2) as an example. In addition to choline chloride / urea (molar ratio 1:1.5-2.5), other systems are also applicable to this invention, such as betaine / glycerol system (molar ratio 1:2-3) and tetrabutylammonium bromide / polyethylene glycol system (molar ratio 1:3-4).

[0109] 3. Prepare the aqueous phase (amine-DES-aqueous solution)

[0110] 3-1) Accurately weigh 0.6g of anhydrous piperazine, dissolve it in 99.4g of deionized water to prepare a piperazine-water solution (i.e., an amine aqueous solution) for later use, wherein the mass percentage concentration of piperazine is 0.6%.

[0111] In addition to 0.6%, other concentrations of piperazine in the prepared piperazine-aqueous solution, such as 0.45-1.5 wt%, are also applicable to this invention.

[0112] 3-2) Place the amine aqueous solution on an electronic balance and slowly add DES (0.5g) dropwise to the amine aqueous solution while stirring. Observe the mass reading of the balance while adding the solution until the reading changes to 0.5g. The mass ratio of DES solvent to piperazine-aqueous solution (i.e. amine aqueous solution) is 0.5:100 (usually it can be (0.2-2.0):100).

[0113] 3-3) After the addition is complete, continue stirring to obtain a homogeneous, free of visible suspended matter ternary mixed solution of piperazine-DES-water (i.e., aqueous phase), for later use. During the stirring process, the stirring temperature is 25±2℃, the stirring speed is 500±20rpm, and the stirring time is 10min (usually 5-15min).

[0114] An aqueous phase system was prepared by mixing an aqueous solution of an amine with DES, wherein the mass fraction of the polyamine compound was 0.45-1.5 wt% and the mass fraction of DES was 0.2-2.0 wt%. The mass ratio refers to the mass proportion of each compound in the mixed aqueous phase system, with DES calculated as the total amount prepared. (The content of DES in the interfacial polymerization has a significant impact on the membrane structure: excessive DES will significantly increase the viscosity of the aqueous phase, delay the reaction process between the polyamine monomer and the acyl halide compound, resulting in an excessively thin selective layer or defects that significantly reduce the retention capacity; while insufficient DES concentration makes it difficult to form an effective hydrogen bond network and fails to play a role in regulating the interfacial polymerization reaction.) The mixed aqueous phase solution was injected into the hollow fiber membrane cavity at a constant flow rate (0.5-1.5 mL / min) using a precision peristaltic pump to ensure that the liquid was fully spread in the membrane cavity.

[0115] The injection time is set to 4-7 min or 2-4 min depending on the target performance (high retention mode or high throughput mode). The timing starts when stable droplets form after the aqueous phase system flows out of the membrane outlet at the other end. (The flow rate gradually stabilizes to 1-3 drops / second and forms regular droplets within 10-15 seconds, with the interval between consecutive droplets fluctuating by ≤±20%), and this is recorded as the timing start point.

[0116] 4. Prepare the oil phase (acyl halide solution).

[0117] Weigh 0.12 g of trimesoyl chloride (TMC), dissolve it in 79.2 g of n-hexane and transfer it to a brown glass bottle for storage. Under light-protected conditions, stir with a magnetic stirrer (400±20 rpm) for (20±5) min until TMC is completely dissolved. Stir until clear and transparent to obtain an oil phase (i.e., acyl halide solution), wherein the mass percentage concentration of TMC in the oil phase is 0.15 wt% (usually (0.1-1) wt%).

[0118] The acyl chloride group in the trimesoyl chloride (TMC) molecule is sensitive to ultraviolet-visible light. Irradiation will cause it to slowly hydrolyze to generate trimesoic acid and release hydrogen chloride, which not only reduces the effective concentration but may also introduce byproduct particles, affecting the reproducibility of subsequent interfacial polymerization. Therefore, it must be prepared in a brown bottle in the dark to inhibit photolysis.

[0119] During the preparation of the oil phase, when the acyl halide (such as aromatic acyl chlorides like TMC, IPC, and TDC) is a directional acyl chloride containing a photosensitive group, light protection is required. Other light-stable acyl halide compounds (such as aliphatic long-chain acyl chlorides and certain amine monomers) do not require light protection.

[0120] TMC has limited solubility in n-hexane. Stirring accelerates solid-liquid mass transfer, prevents localized supersaturation and the precipitation of fine crystals, and ensures a homogeneous and clear solution. Too low a stirring speed (<200 rpm) or too short a stirring time (<10 min) can leave undissolved particles; too high a stirring speed (>600 rpm) will introduce excessive dissolved oxygen and generate bubbles. Experiments have shown that a clear and transparent 0.15 wt% TMC-n-hexane solution can be obtained at room temperature using 400 ± 20 rpm for 20 min.

[0121] 5. Interfacial polymerization reaction

[0122] 5-1): Connect one end of the pretreatment base membrane (i.e., hollow fiber ultrafiltration support membrane) to the peristaltic pump. The end connected to the peristaltic pump is called the injection end of the pretreatment base membrane, and the other end not connected to the peristaltic pump is called the outflow end of the pretreatment base membrane.

[0123] Turn on the peristaltic pump and inject the aqueous phase (amine-DES-aqueous solution, i.e., PIP-DES-aqueous solution) into the membrane cavity from the injection end of the pretreated base membrane. At the same time, observe the outflow of droplets from the base membrane outlet. Start timing when the aqueous phase steadily flows out of the base membrane outlet (called the aqueous phase stable droplet timing). The outflow rate of the aqueous phase at the outlet is 2 drops / second (usually 1-3 drops / second); the aqueous phase injection rate is 1.5 mL / min (usually 1-2 mL / min).

[0124] The aqueous phase liquid begins to flow steadily from the base membrane outlet, which is considered to mean that the aqueous phase has filled and begun to wet the inner cavity of the base membrane.

[0125] 5-2): After the aqueous phase is stabilized and dripped for 5 minutes (i.e., the aqueous phase fills and wets the inner cavity of the base membrane for 5 minutes, usually 4-7 minutes in high retention mode), stop the peristaltic pump and stop injecting the aqueous phase into the inner cavity of the base membrane; then use an air compressor to introduce nitrogen gas at a constant pressure into the inner cavity of the base membrane from the injection end of the base membrane for a second nitrogen purging treatment, wherein the relative pressure of the nitrogen gas introduced is 0.08±0.02MPa (usually 0.06-0.1MPa); the second nitrogen purging time is 3 minutes (usually 2-6 minutes).

[0126] After the aqueous phase system is injected, the inner cavity of the base membrane is immediately purged with high-purity nitrogen at a constant pressure (0.08±0.02MPa) to purge the aqueous phase and ensure that the surface of the membrane cavity is uniformly moistened but without any free liquid residue. This is to prevent residual moisture from reacting with the acyl halide and affecting the interfacial polymerization quality. The specific purging time is determined based on the amount of aqueous phase introduced (aqueous phase introduction time: second nitrogen purging time = 0.5-2:1).

[0127] If the relative pressure of nitrogen is too high during nitrogen purging (greater than 0.1 MPa), the membrane fibers will be subjected to a high transmembrane pressure difference, which can easily lead to mechanical damage, pore structure collapse, or excessive discharge of polyamine solution, resulting in defects in the polyamide layer. If the pressure is less than 0.06 MPa, the purging driving force is insufficient, and the liquid phase in the cavity cannot be driven out in a timely and uniform manner, which can easily lead to droplet retention, leaving behind salting out or monomer crystallization, blocking the pores and reducing the flux.

[0128] This air-blowing drying step not only effectively removes moisture and avoids dilution of the aqueous phase, but also prevents non-selective cross-linking reactions between acyl chloride compounds and residual moisture in the membrane during the subsequent oil phase injection stage, ensuring the controllability of the interfacial polymerization process and the integrity of the membrane.

[0129] 5-3): Connect the peristaltic pump to the base membrane injection end and inject the oil phase (TMC-n-hexane solution) into the inner cavity of the base membrane from the injection end of the pretreated base membrane. At the same time, observe the outflow of droplets from the base membrane outflow end. Start timing when the oil phase steadily flows out of the base membrane (called oil phase stable droplet timing). The oil phase is considered to be steadily flowing out of the outflow end when the flow rate at the outflow end is 2 drops / second (usually 1-3 drops / second); the oil phase injection rate is 1.5mL / min (usually 1-2mL / min).

[0130] When the oil phase liquid begins to flow steadily from the base membrane outflow end, it is considered that the oil phase has filled and begun to wet the inner cavity of the base membrane.

[0131] The starting point for the steady-state dropping timer is the moment when the flow rate of the liquid flowing out of the base film (aqueous phase or oil phase) stabilizes at 1-3 drops / second.

[0132] The oil phase injection time is set according to the target performance (high retention mode / high flux mode), with 4-7 min for high retention mode and 2-4 min for high flux mode. The stable dripping time ratio of aqueous phase to oil phase is dynamically matched at 1:(0.5-2), and the timing starts from the moment when the aqueous / oil phase system flows out of the membrane module at a stable flow rate.

[0133] 5-4): The oil phase stabilization dropping time is 5 min (i.e., the oil phase fills and wets the inner cavity of the base membrane for 5 min, usually 4-7 min in high retention mode). When the oil phase fills and wets the inner cavity of the base membrane, the PIP and TMC (polyamine compound and acyl halide compound) wetted in the inner cavity of the base membrane undergo interfacial polymerization reaction on the surface of the hollow fiber base membrane. The interfacial polymerization reaction takes 5 min (usually 4-7 min in high retention mode) to form an ultrathin polyamide (PA) selective layer. The interfacial polymerization reaction time is also the oil phase stabilization dropping time.

[0134] 5-5) After the interfacial polymerization reaction lasts for 5 minutes (usually 4-7 minutes in high retention mode), turn off the peristaltic pump and stop injecting the oil phase into the inner cavity of the base membrane. Then, use an air compressor to introduce nitrogen gas at a constant pressure into the inner cavity of the base membrane from the injection end of the base membrane for a third nitrogen purging treatment. The relative pressure of the nitrogen gas introduced is 0.08±0.02MPa (usually 0.06-0.1MPa); the third nitrogen purging treatment time is 3 minutes (usually 2-4 minutes in high retention mode).

[0135] The oil phase and the aqueous phase undergo a polymerization reaction on the surface of the hollow fiber base membrane to form an ultrathin polyamide (PA) selective layer. The interfacial polymerization reaction time is 4-7 minutes.

[0136] 5-6): After the third nitrogen purging for 3 minutes (usually 2-4 minutes in high retention mode), let it stand at room temperature (25℃, usually 20-30℃) for at least 4 hours (usually 4-6 hours), that is, dry for 4 hours, to obtain the hollow fiber nanofiltration membrane based on interfacial polymerization regulation of the present invention.

[0137] The purpose of the second nitrogen purging (before oil phase injection) is to promptly introduce nitrogen at a constant pressure after the aqueous phase injection to fully remove the residual aqueous liquid in the inner cavity of the base membrane, resulting in a uniformly slightly moist surface. This avoids bulk side reactions between the acyl chloride monomer and residual water after oil phase injection and ensures that the oil phase and aqueous phase monomer react only at the membrane surface interface. This ensures a clear and stable initiation interface for the interfacial polymerization reaction, resulting in a uniform and dense polyamide layer. If the pressure is greater than 0.1 MPa, the membrane fibers are subjected to a high transmembrane pressure difference, which can easily lead to mechanical damage, pore structure collapse, or excessive discharge of polyamine solution, causing defects in the polyamide layer. If the pressure is less than 0.06 MPa, the purging driving force is insufficient, and the liquid phase in the cavity cannot be driven out in a timely and uniform manner, easily forming droplet retention; leaving behind salting out or monomer crystallization, clogging the pores and reducing flux.

[0138] The purpose of the third nitrogen purging (after the oil phase reaction is completed) is to remove residual oil phase solution and unreacted monomers from the base membrane cavity by re-introducing nitrogen after the interfacial polymerization reaction. This also removes reaction byproducts, rapidly removes residual solvent from the membrane surface, and promotes the initial solidification and shaping of the newly formed polyamide selective layer. This effectively reduces local thickness unevenness or membrane defects, and improves the structural stability and separation performance of the selective layer. If the pressure of the third purging is >0.1 MPa, the membrane fibers are subjected to a high transmembrane pressure difference, which can easily cause mechanical damage, pore structure collapse, and excessive discharge of unreacted oil phase, leading to defects in the nascent polyamide layer. If the pressure is <0.06 MPa, the purging driving force is insufficient, and residual liquid in the cavity cannot be discharged in a timely and uniform manner, easily forming droplet retention accompanied by salting out or monomer crystallization, clogging the pores and reducing flux.

[0139] The biodegradable properties of the eutectic solvent (DES) of this invention ensure no solvent residue.

[0140] The method of this invention precisely controls the contact time between the aqueous and oil phases and introduces a eutectic solvent (DES) into the system. By utilizing its dynamic hydrogen bond network to construct a reversible physical barrier at the interface, the diffusion rate of monomers is slowed down and the reaction interface is stabilized. Thus, the interfacial polymerization rate can be controlled without additional organic additives.

[0141] Example 1A: Preparation of high-flux hollow fiber nanofiltration membrane

[0142] 1. Pretreatment of hollow fiber ultrafiltration membrane

[0143] Same as Example 1.

[0144] 2. Preparation of eutectic solvent (DES)

[0145] Same as Example 1.

[0146] 3. Prepare the aqueous phase (amine-DES-aqueous solution)

[0147] Same as Example 1.

[0148] 4. Prepare the oil phase (acyl halide solution).

[0149] Same as Example 1.

[0150] 5. Interfacial polymerization reaction

[0151] Except for the following steps: the timing of the aqueous phase stable droplet in step 5-2) is 3 min (usually 2-4 min in high-throughput mode); the timing of the oil phase stable droplet in step 5-4) is 3 min (usually 2-4 min in high-throughput mode); and the timing of the third nitrogen purging in step 5-5) is 1 min (usually 1-2 min in high-throughput mode), the rest are the same as in Example 1.

[0152] In the interfacial polymerization process for preparing hollow fiber nanofiltration membranes, the aqueous phase injection time, oil phase injection time, and nitrogen purging time have a significant impact on membrane performance. The aqueous phase injection time (the time for stabilizing the aqueous phase droplets) determines the enrichment and diffusion depth of hydrophilic monomers on the membrane surface, thus affecting the thickness and structural uniformity of the polyamide layer. The oil phase injection time (the time for stabilizing the oil phase droplets) regulates the initiation timing and duration of the interfacial reaction, directly affecting the degree of crosslinking and membrane density. The nitrogen purging process is used to remove residual moisture and non-reactive liquids, prevent side reactions, and help stabilize the interfacial state.

[0153] Since interfacial polymerization reactions are highly dependent on transient diffusion and reaction kinetic equilibrium, even small differences in process parameters can lead to significant changes in the selective layer structure and separation performance. This is especially true in hollow fiber curved structures, where the non-uniform interfacial environment makes parameter control even more critical.

[0154] Hollow fiber nanofiltration membrane with high retention mode prepared according to Example 1

[0155] This embodiment aims to examine the changes in membrane performance under DES-free conditions while maintaining short contact time parameters, in order to compare them with high retention and high flux modes with added DES.

[0156] Except for the absence of DES, the preparation method is the same as in Example 1, and is as follows:

[0157] 1. Pretreatment of hollow fiber ultrafiltration membrane

[0158] Same as Example 1.

[0159] 2. Prepare the aqueous phase (amine-aqueous solution).

[0160] Accurately weigh 0.6g of anhydrous piperazine, dissolve it in 99.4g of deionized water, and stir until a clear and transparent piperazine-water binary mixed solution is formed. Set aside for later use, wherein the mass percentage concentration of piperazine is 0.6%.

[0161] 3. Prepare the oil phase (acyl halide solution).

[0162] The same as step 4) in Example 1.

[0163] 4. Interfacial polymerization reaction

[0164] The same as step 5) in Example 1.

[0165] High-flux hollow fiber nanofiltration membrane prepared according to Example 1A

[0166] Except for the absence of DES, the preparation method is the same as in Example 1A, as follows:

[0167] 1. Pretreatment of hollow fiber ultrafiltration membrane

[0168] Same as Example 1A.

[0169] 2. Prepare the aqueous phase (amine-aqueous solution).

[0170] Accurately weigh 0.6 g of anhydrous piperazine and dissolve it in 99.4 g of deionized water. Stir until a clear and transparent binary mixture of piperazine and water is formed, with a piperazine mass percentage concentration of 0.6%.

[0171] 3. Prepare the oil phase (acyl halide solution).

[0172] The same as step 4) of Example 1A.

[0173] 4. Interfacial polymerization reaction

[0174] The same as step 5) of Example 1A.

[0175] Example 2: Preparation of hollow fiber nanofiltration membrane with high retention mode

[0176] Except for step 1), in which the commercially available ultrafiltration base membrane is replaced with a commercially available polyethersulfone (PES) hollow fiber ultrafiltration base membrane (MWCO 15kDa, inner diameter 1.4mm, outer diameter 2.0mm), the rest is the same as in Example 1.

[0177] Example 2A: Preparation of a high-flux hollow fiber nanofiltration membrane

[0178] Except for the following steps: the timing of the aqueous phase stable droplet in step 5-2) is 3 min (usually 2-4 min in high-throughput mode); the timing of the oil phase stable droplet in step 5-4) is 3 min (usually 2-4 min in high-throughput mode); and the timing of the third nitrogen purging in step 5-5) is 1 min (usually 1-2 min in high-throughput mode), the rest are the same as in Example 2.

[0179] Hollow fiber nanofiltration membrane with high retention mode prepared according to Example 2

[0180] Except for not adding DES, it is the same as Example 2.

[0181] 1. Pretreatment of hollow fiber ultrafiltration membrane

[0182] Same as Example 2.

[0183] 2. Prepare the aqueous phase (amine-aqueous solution).

[0184] Accurately weigh 0.6 g of anhydrous piperazine and dissolve it in 99.4 g of deionized water. Stir until a clear and transparent binary mixture of piperazine and water is formed, with a piperazine mass percentage concentration of 0.6%.

[0185] 3. Prepare the oil phase (acyl halide solution).

[0186] The same as step 4) in Example 2.

[0187] 4. Interfacial polymerization reaction

[0188] The same as step 5) in Example 2.

[0189] Comparative Example 2A: Preparation of a high-flux hollow fiber nanofiltration membrane

[0190] Except for not adding DES, it is the same as Example 2A.

[0191] 1. Pretreatment of hollow fiber ultrafiltration membrane

[0192] Same as Example 2A.

[0193] 2. Prepare the aqueous phase (amine-aqueous solution).

[0194] Accurately weigh 0.6 g of anhydrous piperazine and dissolve it in 99.4 g of deionized water. Stir until a clear and transparent binary mixture of piperazine and water is formed, with a piperazine mass percentage concentration of 0.6%.

[0195] 3. Prepare the oil phase (acyl halide solution).

[0196] The same as step 4) of Example 2A.

[0197] 4. Interfacial polymerization reaction

[0198] The same as step 5) of Example 2A.

[0199] Characterization of hollow fiber nanofiltration membrane in Experiment Example 1

[0200] The performance of the hollow fiber nanofiltration membranes prepared in Examples 1, 1A; 2, 2A; and Control Examples 1, 1A; 2, 2A was determined according to the following method:

[0201] 1. Water contact angle

[0202] The hydrophilicity and hydrophobicity of membranes under different conditions were evaluated using a Water Contact Analyzer (WCA) model OCA50 from Dataphysics GmbH, Germany. Wetting behavior of 0.8 μL ultrapure water droplets at the initial contact moment (t = 0 s) with the membrane surface was recorded under constant temperature conditions. The static water contact angle was calculated by automatically fitting the droplet profile using the Young-Laplace equation.

[0203] 2. Zeta potential measurement

[0204] The surface charge properties of hollow fiber nanofiltration membranes were determined using a Malvern Instruments ZS90 Zeta potential analyzer. A 0.075 M KCl solution was used as the background electrolyte. The pH of the system was adjusted to neutral (7.0 ± 0.1) by micro-titration with 0.1 M HCl / NaOH solution. The Zeta potential distribution of the hollow fiber nanofiltration membrane at the solid-liquid interface was measured under isothermal conditions at 25 °C.

[0205] 3. MWCO (Molecular Weight Cutoff)

[0206] Molecular cutoff experiments were performed using PEG (polyethylene glycol) series to estimate the molecular weight cutoff (MWCO).

[0207] The membrane retention characteristics were characterized using molecular weight fractionated polyethylene glycol (PEG 200 / 400 / 600Da). A 1 g / L PEG solution was prepared and cross-flow filtration experiments were conducted at a constant temperature of 25.0 ± 0.3 °C and a transmembrane pressure of 0.45 MPa. After the permeate was pretreated with a 0.22 μm nylon filter membrane, the total organic carbon concentration was determined using a Shimadzu TOC-L CPH total organic analyzer. The solute rejection rate was calculated using formula (1). When the rejection rate of a certain molecular weight PEG reached 90%, the molecular weight was determined to be the MWCO value.

[0208]

[0209] r p =16.73×10 -12 ×MWCO 0.577 (2)

[0210] In formula (1): R is the rejection rate (%), and C1 and C2 are the organic matter concentrations (mg / L) of the feed liquid and permeate, respectively. In formula (2): rp (nm) represents the Stokes radius of the solute.

[0211] 4. Film thickness

[0212] The cross-section of the membrane was observed using a scanning electron microscope (SEM). The membrane sample was rapidly frozen in liquid nitrogen (approximately 30 seconds). Taking advantage of its brittle fracture properties, the sample was cut along the direction perpendicular to the membrane surface using a sharp blade or tweezers to expose the cross-section. The membrane thickness d was directly measured on the SEM image using a software ruler tool (such as ImageJ or Nano Measurer). The calculation formula is (6).

[0213]

[0214] The measurement results are shown in Table 1.

[0215] Table 1. Performance test results of hollow fiber nanofiltration membranes based on interface polymerization regulation

[0216]

[0217]

[0218] Experiment 2: Na₂SO₄ and NaCl rejection rates and flux of hollow fiber nanofiltration membranes

[0219] 1. Preparation of Na₂SO₄ solution and NaCl solution

[0220] Prepare a Na2SO4 solution with a concentration of 2000 ppm and a NaCl solution with a concentration of 2000 mg / L, respectively, ensuring that they are at room temperature (25±2℃) during the test and that the solutions are stirred evenly to avoid precipitation or uneven concentration.

[0221] 2. Membrane pure water pre-pressurization operation

[0222] Before conducting performance testing of the nanofiltration membrane, a pure water pre-compression operation was performed to ensure that the membrane's pore size and structure were stable. A BONA-GM-58 membrane separation device from China was used. The hollow fiber nanofiltration membranes prepared in Examples 1 / 1A, 1 / 2A, and Control Examples 1 / 1A and 2 / 2A were fixed to the membrane interface of the device, and pure water was poured into the feed tank. The pre-compression process involved applying a certain pressure to both ends of the prepared hollow fiber nanofiltration membrane, applying a pressure of 0.5 MPa (typically operated at room temperature of 25°C), and maintaining this pressure for 30-45 minutes to ensure stable flux.

[0223] 3. Retention rate and flux measurement

[0224] Once the flux stabilized, the pressure was adjusted to 0.6 MPa, and the prepared sodium sulfate or sodium chloride solution was poured into the feed tank. After the flow rate stabilized, timing was started and permeate collection began. After 10 minutes, the permeate volume was measured, and the flux was calculated. The permeate conductivity was measured, and the rejection rate was calculated. The measurement results are shown in Table 2.

[0225] Table 2 shows the rejection rates of hollow fiber nanofiltration membranes.

[0226]

[0227] Based on the Na2SO4 and NaCl retention rate and flux test results in Table 2, it can be seen that the nanofiltration membranes (Examples 1, 1A, 2, 2A) prepared by using eutectic solvent (DES) intervention and optimized interfacial polymerization time control in this invention exhibit the following significant advantages compared with traditional preparation methods (Control Examples 1, 1A, 2, 2A):

[0228] 1. High and adjustable sodium sulfate retention rate

[0229] High retention mode (Examples 1 and 2): Retention rates reached 95–98% (Group 1) and 93–96% (Group 2), significantly better than the control group's 85–90% and 88–92%. This indicates that after DES intervention, interfacial polymerization resulted in a denser PA layer, significantly improving sodium sulfate desalination performance. High throughput mode (Examples 1A and 2A): Although the retention rate decreased to 50–70%, it still showed a 5–10% improvement compared to the control group's similar mode (Control Examples 1A and 2A), demonstrating adjustable separation performance.

[0230] 2. Increased NaCl retention rate

[0231] The high retention mode of the present invention (Examples 1 and 2) increases the NaCl retention rate to 40–50%, which is a significant improvement compared to Control Examples 1 and 2 (30–40%). The high throughput mode (Examples 1A and 2A) is also superior to Control Examples 1A and 2A, especially in the separation performance of low salt (NaCl), indicating that the interface structure is more finely controlled.

[0232] 3. Flux significantly increased

[0233] In high rejection mode: the flux of Examples 1 and 2 is 32–55 L / m³. 2 •h, compared to 20–30 L / m in Control Examples 1 and 2 2 •h, increased by 40–80%. In high-throughput mode: the throughput of Examples 1A and 2A is as high as 50–60 L / m 2 •h, significantly better than the 30–45 L / m of control examples 1A and 2A. 2 ·h.

[0234] This invention demonstrates that by using DES and time optimization, it overcomes the traditional trade-off between "high rejection rate" and "high throughput".

[0235] 4. Enhanced performance control capabilities

[0236] The method of this invention can achieve two different performance modes by adjusting the aqueous / oil phase time ratio and the concentration of DES: high retention type (1, 2): high selectivity, suitable for high-salinity wastewater treatment; high flux type (1A, 2A): significantly improved flux, suitable for low-salinity, high-flow-rate water supply scenarios. Traditional methods, on the other hand, have limited ability to adjust flux and retention rate, resulting in a narrow performance range.

[0237] These performance advantages stem from the fact that DES regulates monomer diffusion kinetics, resulting in a more uniform film layer and more controllable interfacial polymerization.

[0238] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a hollow fiber nanofiltration membrane based on interfacial polymerization regulation, characterized in that, include: First, prepare an aqueous system by mixing an aqueous amine solution with a eutectic solvent. Next: the acyl halide compound is mixed with an organic solvent, dissolved, and prepared into an oil phase system; Then, the aqueous phase system and the oil phase system are injected into the hollow fiber ultrafiltration membrane in sequence. The acyl halide compounds in the oil phase system and the amine compounds in the aqueous phase system undergo interfacial polymerization on the surface of the hollow fiber ultrafiltration membrane to form a polyamide selective film, thus obtaining a hollow fiber nanofiltration membrane based on interfacial polymerization control.

2. The preparation method according to claim 1, characterized in that, The amine aqueous solution is prepared by mixing a polyamine compound with deionized water, wherein the mass percentage concentration of the polyamine compound in the amine aqueous solution is (0.45-1.5) wt%.

3. The preparation method according to claim 1 or 2, characterized in that, The acyl halide compound is one or more of the following: trimesoyl chloride (TMC), isophthaloyl chloride, terephthaloyl chloride, 1,3,5-cyclohexanetricarboxyl chloride, or 1,2,3,4-cyclohexanetetracarboxyl chloride, preferably trimesoyl chloride; the organic solvent is one or more of the following nonpolar solvents: n-hexane, isooctane, cyclohexane, n-octane, or n-nonane, preferably n-hexane.

4. A method for preparing a hollow fiber nanofiltration membrane based on interfacial polymerization regulation, characterized in that, Includes the following steps: 1) Preparation of eutectic solvent The hydrogen bond donor and the hydrogen bond acceptor are mixed evenly to prepare a eutectic solvent; 2) Preparation of aqueous system A eutectic solvent is added to an aqueous amine solution and mixed thoroughly to prepare an aqueous system. 3) Preparation of oil phase system The acyl halide compound is dissolved in an organic solvent, mixed thoroughly, and prepared into an oil phase system; 4) Interfacial polymerization reaction 4-1) Inject the aqueous phase system into the inner cavity of the hollow fiber ultrafiltration membrane from one end, that is, inject the aqueous phase system into the inner cavity of the ultrafiltration membrane from the injection end of the base membrane. At the same time, observe the outflow of the aqueous phase system from the other end of the base membrane, that is, the outflow end of the base membrane. Start timing when the aqueous phase system flows out from the outflow end of the base membrane at a stable flow rate. This is recorded as the time for the aqueous phase to drop steadily. 4-2): After the aqueous phase is stabilized and dripped for 2-7 minutes, the aqueous phase system is injected into the base membrane cavity for 2-7 minutes. After the aqueous phase fills and wets the base membrane cavity, the injection of the aqueous phase system into the base membrane cavity is stopped, and nitrogen gas is introduced into the base membrane cavity from the base membrane injection end to perform nitrogen purging treatment after aqueous phase injection. 4-3) After nitrogen purging, the oil phase system is injected into the inner cavity of the hollow fiber ultrafiltration membrane from the injection end, that is, the oil phase system is injected into the inner cavity of the ultrafiltration membrane from the injection end of the base membrane. At the same time, the outflow of the oil phase system at the other end of the base membrane, that is, the outflow end of the base membrane, is observed. The timer starts when the oil phase system flows out from the outflow end of the base membrane at a stable flow rate, and is recorded as the oil phase stable droplet time. 4-4) The oil phase is stabilized and dripped for 2-7 minutes. That is, the oil phase system is injected into the inner cavity of the base membrane for 2-7 minutes. The oil phase fills and wets the inner cavity of the base membrane. The acyl halide compounds in the oil phase system and the polyamine compounds in the aqueous phase system in the hollow fiber ultrafiltration membrane undergo interfacial polymerization reaction on the surface of the hollow fiber ultrafiltration membrane to form a polyamide selective film. 4-5) After the interfacial polymerization reaction for 2-7 minutes, stop injecting the oil phase system into the inner cavity of the base membrane, and introduce nitrogen gas into the inner cavity of the base membrane from the injection end of the base membrane to perform nitrogen purging treatment after oil phase injection.

5. The preparation method according to claim 4, characterized in that, The hydrogen bond donor in step 1) is an organic small molecule compound having hydroxyl, carboxyl, amino or amide groups; the hydrogen bond acceptor is a quaternary ammonium salt compound.

6. The preparation method according to claim 4 or 5, characterized in that, In step 2), the mass ratio of the eutectic solvent to the amine aqueous solution in the aqueous phase system is (0.2-2.0):100, preferably (0.2-1.0):100, and more preferably 0.5:

100.

7. The preparation method according to claim 4 or 5, characterized in that, In step 4-1), the injection rate of the aqueous phase system is 0.5-2 mL / min.

8. The preparation method according to claim 4 or 5, characterized in that, In step 4-2), the relative pressure of nitrogen during the nitrogen purging process is 0.08±0.02MPa; the nitrogen purging time is 2-6min.

9. The preparation method according to claim 4 or 5, characterized in that, In step 4-3), the oil phase system is injected at a rate of 0.5-2 mL / min; in step 4-4), the interfacial polymerization reaction time is 2-7 min.

10. A hollow fiber nanofiltration membrane based on interface polymerization regulation, characterized in that, Prepared according to the method described in any one of claims 1-9.

Citation Information

Cited By

  • Composite membrane as well as preparation method and application thereof

    CN122230545A

  • Composite membranes, their preparation methods and applications

    CN122230545B